"Cage in Box" – A modification of AIIMS BOX technique for large gap nonunion in young patients with neglected femur neck fractures. Issue 3 (March 2022) - Garg, Bhavuk; Vatsya, Pulak
Highlights: Young patients with neck of femur fractures are more prone to complications from this fracture than their older counterparts, primarily due to the high velocity of trauma and nature of the fracture. In these patients, arthroplasty is not the first option as head salvage is considered much more essential. Multiple methods to manage these fractures and the neglected variety have been described in the literature. We describe a modification of one of our already described technique – the AIIMS BOX technique. We feel this technique provides adequate mechanical stability, length gain and good outcomes once the surgeon has enough understanding of the basic principles of our technique. Abstract: Neck of femur fractures have often been termed as "The Unsolved Fractures", since they have a guarded outcome even after improved understanding of biomechanics and biology of this area. Gap-nonunion is one such dreaded complication of this fracture, especially in younger (<60 years) population, where arthroplasty may not be the best go-to option. We have earlier described "The AIIMS BOX" technique to manage such cases of gap non-union in neglected neck femur fractures [1] . Here we intend to describe a more successful modification of this technique. We operated 7 cases of gap non-union with our new "Cage in Box" strategy and followed these cases for 5 years. 6 patients from this group achieved excellent to good outcomes and only 1 reported a poor outcome. All the patients, except the one with poor outcome, could walk without aid and do activities of daily living independently. 3 patients developed AVN but had no evidence of collapse. 3 patients also developed Coxa vara, but it was significant only in one case. 6/7 patients were able to squat. We describe this method in detail and feel this can be a viable option in the armamentarium of orthopedic surgeons, along with valgus osteotomy, vascularized and non-vascularized fibular strut graft as well as Meyer's Graft, to help them solve this unsolved fracture.